نطاق ولاية القاضي الشرعي في تايلاند وماليزيا: دراسة مقارنة = Nitaq wilayah al-qadhi al-syari' fi Thailand wa-Maliziya - Hama, Zakariya; Laeba, Muhammad (2010)
The main objective of this research was to examine and compare the jurisdiction of Shariah Judges in Thailand and Malaysia. The research applied the qualitative approach with analytical and field method .Documentary research was based on Al-Quran, Al-Sunnah, Primary, Secondary, and Contemporary sources of the Islamic law whereas the in-depth interview with Thai and Malaysian Judges were applied to supplement the analysis and comparison. The results reveal that The Shariah Judge in Thailand can only deal in cases where the parties are Thai Muslims and live in the four southern border provinces, namely Pattani, Narathiwat, Yala, and Satun. Moreover, those cases must relate only to the Islamic Family law. The Shariah Judge can only deal in the Islamic law matter without trying to find out the facts when those fall under the power of civil judge. It means that both, the Shariah and Civil judges, have to sit together in order to make a decision on the same case. In addition, the decision of Shariah Judge cannot be appeal. On the other hand, the jurisdiction of Shariah Judge in Malaysia covers all Malaysian Muslims and the cases involve in the Islamic family law, anything related to it and some criminal laws in which related to Islam. Moreover, the decision made under the Shariah Judge can still be appeal to the Shariah High Court. Suggestions were made to cover the jurisdiction of Shariah Judge in Thailand to all Muslim in Thailand, to empower them to deal with the fact in the cases as they do in the Islamic law matter and give chances to parties in appealing cases to Shariah High Court. The other suggestion that to cover the jurisdiction of Shariah Judge in Thailand and Malaysia to all cases related to Sharaih law not only to the Islamic Family Law and some cases of criminal law and punish the criminal with suitable punishment according to the Islamic law.